Factors In Games That Effect Game Based Learning In Malaysia - Akbar, Ameen (2011)
In this thesis we will explore the models, concepts and principles that have been used by past and present game based learning endeavours all over the world, from this we will identify the key factors and elements in games that create the phenomenon of learning. A survey will be conducted in order to identify the effectiveness these factors on a Malaysian audience.